PENGARUH AKUPRESUR TITIK Ht 7 DAN TITIK Li 4 TERHADAP INTENSITAS NYERI LUKA POST SECTIO CAESARIA DI RUMAH SAKIT PURI BUNDA DENPASAR TAHUN 2022 - Ni Komang Dewi Listyani; Ni Wayan Suarniti; Listina Ade Widya Ningtyas (Midwifery Department of Health Polytechnic, Ministry of Health, Denpasar, 2023)
The caesarean section surgical procedure results in a side that will cause a break in body tissue which results in pain. The pain felt by mothers after caesarean section causes them to be lazy and afraid to carry out early mobilization after caesarean section and also causes lactation problems. Acupressure is carried out by physical pressure on several points on the surface of the body which are places for energy circulation and balance in cases of pain symptoms. This type of research is quasi experiment one group pre and post test. The population is all post-cesarean section mothers at Puri Bunda Hospital, a sample of every post-cesarean section mother who is willing to be a respondent. Data analysis used the Willcoxon test. The majority of post-cesarean section mothers (64.5%) felt moderate pain before being given intervention with acupressure, and 11 people (35.5%) felt severe pain. More than half experienced moderate pain (51.6%) and 15 people experienced mild pain (48.4%) after being given acupressure. The Wilcoxon test results obtained a value of p = 0.002, namely that there was an effect of acupressure on the intensity of pain in post-cesarean section mothers. There is an influence of acupressure at the Ht 7 and Li 4 points on the intensity of pain in women after caesarean section at Puri Bunda Hospital, Denpasar in 2022. Suggestion: Midwifery service places should provide acupressure to reduce pain after caesarean section.